2021
DOI: 10.2174/1874609814666210624121603
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Aging on Body Temperature: A Systematic Review and Meta- Analysis

Abstract: Background: Since age is the major risk factor for chronic diseases and mortality, older adults having lower basal temperature than young individuals seems to be a misconception. Many confounding factors could hinder the achievement of a consensus, such as the different sites of measurement, control of basal conditions, health conditions, age difference compared, sex, and others. Objective: The aim was to meta-analyze previous studies in order to find a consensus regarding the effects of aging on body tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…However, body mass gain and VAT lipid accumulation were decreased by GABA treatment in aged HFD-fed mice. Moreover, other important physiological changes, such as a body temperature decrease, occur with age [41]. Consistently, we identified in the present study that body temperature was decreased in aged mice relative to that in young mice.…”
Section: Discussionsupporting
confidence: 92%
“…However, body mass gain and VAT lipid accumulation were decreased by GABA treatment in aged HFD-fed mice. Moreover, other important physiological changes, such as a body temperature decrease, occur with age [41]. Consistently, we identified in the present study that body temperature was decreased in aged mice relative to that in young mice.…”
Section: Discussionsupporting
confidence: 92%
“…Age showed a negative correlation with the skin temperature of the knee, with younger patients having higher temperatures compared to older patients. The lower temperature of the knees of elderly patients is ascribable to the decrease in body temperature with aging, probably due to a reduction in basal metabolic rate and a lower muscle component compared to the younger population [ 21 , 22 , 23 ]. Moreover, a reduction in the overall skin temperature with aging has been justified by the reduction in core temperature in older adults due to a reduction in metabolic processes and to an alteration in the heat dissipation through the skin [ 22 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lower temperature of the knees of elderly patients is ascribable to the decrease in body temperature with aging, probably due to a reduction in basal metabolic rate and a lower muscle component compared to the younger population [ 21 , 22 , 23 ]. Moreover, a reduction in the overall skin temperature with aging has been justified by the reduction in core temperature in older adults due to a reduction in metabolic processes and to an alteration in the heat dissipation through the skin [ 22 , 24 , 25 ]. This was reported in healthy subjects by Ferreira et al, who found that young subjects’ limbs’ temperature was higher compared to the elderly subjects’ limbs [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, numerous factors can affect a person's temperature, including medications, the environment, exercise, skin color, gender, race, and body temperature variations throughout the day and month [8][9][10][11]. Moreover, there are differences in people's individual basal body temperatures, which presents an even greater challenge in older adults due to increased variation in their baseline temperatures [12].…”
mentioning
confidence: 99%